2012
DOI: 10.1073/pnas.1213841110
|View full text |Cite
|
Sign up to set email alerts
|

Joint analysis of stressors and ecosystem services to enhance restoration effectiveness

Abstract: With increasing pressure placed on natural systems by growing human populations, both scientists and resource managers need a better understanding of the relationships between cumulative stress from human activities and valued ecosystem services. Societies often seek to mitigate threats to these services through largescale, costly restoration projects, such as the over one billion dollar Great Lakes Restoration Initiative currently underway. To help inform these efforts, we merged high-resolution spatial analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
244
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 317 publications
(246 citation statements)
references
References 18 publications
2
244
0
Order By: Relevance
“…These regions are more ecologically vulnerable, and sensitive to climate change and human activities, the health of which is a critical challenge (Reynolds et al, 2007;Liang et al, 2015;Yang et al, 2014Yang et al, , 2016. In order to address the serious environmental and ecological issues, a series of large-scale ecological restoration projects were carried out throughout the world (Allana et al, 2013), and China has also taken efforts in such actions since the 1950s (Huang et al, 2009). Recently, two large-scale ecological restoration projects, i.e., the Natural Forest Conservation (NFC) project and the Grain for Green (GFG) project, have been launched to improve vegetation coverage in the Loess Plateau of North China (Feng et al, 2013;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These regions are more ecologically vulnerable, and sensitive to climate change and human activities, the health of which is a critical challenge (Reynolds et al, 2007;Liang et al, 2015;Yang et al, 2014Yang et al, , 2016. In order to address the serious environmental and ecological issues, a series of large-scale ecological restoration projects were carried out throughout the world (Allana et al, 2013), and China has also taken efforts in such actions since the 1950s (Huang et al, 2009). Recently, two large-scale ecological restoration projects, i.e., the Natural Forest Conservation (NFC) project and the Grain for Green (GFG) project, have been launched to improve vegetation coverage in the Loess Plateau of North China (Feng et al, 2013;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Allan et al (2013) modeled current environmental stressors affecting the Great Lakes and found that cumulative stress levels were greatest in nearshore regions and generally decreased with distance from the shore. Only one investigation concerning microplastics pollution in Lake Ontario sediments has been published to date , despite it being the terminal lake within the Great Lakes system.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is critical that we understand how accelerating land-based stressors will affect living resources in coastal ecosystems. Estuaries and other coastal areas are rapidly changing in response to intensifying stressors linked to human activities at both local and global scales (Lotze et al 2006;Halpern et al 2008;Barbier et al 2011;Allan et al 2013). Human population centers are already located predominantly in coastal areas, and population density near coasts continues to rapidly increase (Crossett et al 2004).…”
Section: Introductionmentioning
confidence: 99%